Engineering Donor–Acceptor Heterostructure Metal–Organic Framework Crystals for Photonic Logic Computation. (17th July 2019) - Liu, Xiao‐Ting; Wang, Kang; Chang, Ze; Zhang, Ying‐Hui; Xu, Jialiang; Zhao, Yong Sheng; Bu, Xian‐He
Abstract: Photonic materials use photons as information carriers and offer the potential for unprecedented applications in optical and optoelectronic devices. In this study, we introduce a new strategy for photonic materials using metal–organic frameworks (MOFs) as the host for the rational construction of donor–acceptor (D–A) heterostructure crystals. We have engineered a rich library of heterostructure crystals using the MOF NKU‐111 as a host. NKU‐111 is based upon an electron‐deficient tridentate ligand (acceptor) that can bind to various electron‐rich guests (donors). The resulting heterocrystals exhibit spatially segregated multi‐color emission resulting from the guest‐dependent charge‐transfer (CT) emission. Spatially effective mono‐directional energy transfer results from tuning the energy gradient between adjacent domains through the selection of donor guest molecules, which suggests potential applications in integrated optical circuit devices, for example, photonic diodes, on‐chip signal processing, optical logic gates. Abstract : MOF‐Logik : Eine kristalline, aus einem Metall‐organischen Gerüst (MOF) bestehende Wirt‐Gast‐Plattform wird für den Aufbau einer Bibliothek von Donor‐Akzeptor(D‐A)‐Heterostrukturkristallen genutzt. Der Ansatz ermöglicht die Konstruktion von Heterokristall‐Bauelementen für die optische logische Datenverarbeitung.